KONSEP ISLAM TENTANG ADAT: Telaah Adat Dan 'Urf Sebagai Sumber Hukum Islam - Faiz Zainuddin (LP2M Universitas Ibrahimy, 2015)
The needs of society very complete and changing is impossible to make law codification perfectly, one of the cause is the difference between local customs are not same with the ancient customs ( Arabicâ€™s custom). This change is not only related to the values, but also can change the religionâ€™s law ( Islam ). So, to solve this problems, it needs the special handling who related the growing problem in the society in terms of Islamic law study. The goal is the problem can be solved by the best decision and can give the solution who is able to runned by society.Furthermore, to give the best solution about the difference needs in the society, so IslamÂ gives a law breakthrough by considering customs as Islamic law basis. This customs becomes law source after Al-Quran and Al- Hadist, because the customs has important role in the process of decline verse. This research was conducted to know how far the influence ofÂ customs toward dynamics of islamic law. This research used explanatory research by applied qualitative research and the research result analysis used analysis content. This research showed that the customs can be used as â€œHujjahâ€ in islamic law as long as no â€œSharihâ€ explanation about the certain case and did not contrary with qhatâ€™iy argument in the form of muqayyadÂ not absolute) and special (not general). Based on the research result, the researcher give suggestion for the law practitioners, if they want to decide law is hoped to more concerned societiesâ€™ customs themselves, and not directed to others, in order to they can give a decision who can be runned by society.